Fresno County Bar Association Law Day Luncheon with U.S. Attorney David Levy at Fresno Hilton Ballroom - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy announcing the Association's Liberty Bell Award goes to Channel 18's General Manager Colin Daugherty Seated is Sandra Snyder